1997
DOI: 10.1016/s0092-8674(00)81894-2
|View full text |Cite
|
Sign up to set email alerts
|

Revertant Mosaicism in Epidermolysis Bullosa Caused by Mitotic Gene Conversion

Abstract: Mitotic gene conversion acting as reverse mutation has not been previously demonstrated in human. We report here that the revertant mosaicism of a compound heterozygous proband with an autosomal recessive genodermatosis, generalized atrophic benign epidermolysis bullosa, is caused by mitotic gene conversion of one of the two mutated COL17A1 alleles. Specifically, the maternal allele surrounding the mutation site on COL17A1 (1706delA) showed reversion of the mutation and loss of heterozygosity along a tract of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
210
1
8

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(221 citation statements)
references
References 30 publications
(7 reference statements)
2
210
1
8
Order By: Relevance
“…Revertant mosaicism has been reported in various diseases including severe combined immunodeficiency [both X linked and adenosine deaminase (ADA) deficiency; refs. 16, 17, and 27], Duchenne muscular dystrophy (28), tyrosinemia (20), Bloom syndrome (19), and epidermolysis bullosa (18,29) among others. In each of these cases, restoration of a normal allele was demonstrated in cells of a single lineage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Revertant mosaicism has been reported in various diseases including severe combined immunodeficiency [both X linked and adenosine deaminase (ADA) deficiency; refs. 16, 17, and 27], Duchenne muscular dystrophy (28), tyrosinemia (20), Bloom syndrome (19), and epidermolysis bullosa (18,29) among others. In each of these cases, restoration of a normal allele was demonstrated in cells of a single lineage.…”
Section: Discussionmentioning
confidence: 99%
“…In each of these cases, restoration of a normal allele was demonstrated in cells of a single lineage. In some of these reports, evidence suggesting a mechanism for the reversion was presented, including mitotic gene conversion (18), back mutation (20,27), intragenic mitotic recombination (19), and the introduction of compensatory mutations (28,29). Each of these mechanisms can result in the restoration of one allele coding for a functional product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most COL17A1 mutations described to date are nonsense and deletion mutations leading to premature termination of translation and absence of type XVII collagen from the skin (Darling et al, 1997;Floeth et al, 1998;Gatalica et al, 1997;Jonkman et al, 1997;McGrath et al, 1995McGrath et al, , 1996aMcGrath et al, , 1996bScheffer et al, 1997;Schumann et al, 1997;Shimizu et al, 1998 887 acceptor splice-site mutations (Chavanas et al, 1997;Darling et al, 1998;Pulkkinen et al, 1999), one donor splice-site mutation (Pulkkinen et al, 1999), and four missense mutations (Floeth et al, 1998;McGrath et al, 1996a;Schumann et al, 1997;Tasanen et al, 2000) have been reported. In only one (Schumann et al, 1997) of the patients could type XVII collagen be immunologically detected in skin or cultured keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 Deletions between direct repeats can also result from RAD51-independent, non-conservative HR pathways, such as sister chromatid replication slippage or single-strand annealing (SSA). 7 Gene conversion, which involves the unidirectional transfer of information from one gene to another, can act as a natural gene therapy process, leading to the correction of deleterious mutations, 8,9 but can also propagate such mutations, culminating in loss of heterozygosity, genetic diseases and cancer. [10][11][12][13][14][15] Given the genome-destabilizing effects of ectopic HR, it is important that such events occur at low rates relative to allelic HR or sister chromatids exchange (SCE).…”
Section: Introductionmentioning
confidence: 99%